Máquinas errantes de agua (2020)
Guided by the intuition of errors, the architectural project is modeled through two programs that seem incompatible but fundamental for citizens: water and violence, considering that, in an erratic place like the San Bernardo neighborhood in Bogotá (Colombia), these two things unite us. This project resists with a Punk attitude to the groundless speculations of the city planners. With this idea in mind, the proposal is to build a series of artifacts that are articulated like a water machine to promote more democratic spaces that allow erratic behavior in the city. The artifacts are connected to the irregular infrastructure that carries the underground waters of the San Agustín river, to make use of a common good that will be scarce in the coming years: water. Also, the project promotes spaces where violence can be manifested in the shape of partying or fighting, acknowledging this is a condition that runs through us all.